Samopoškodovalno vedenje mladostnikov kot posledica družinskega nasilja - Zavratnik, Špela (Obzornik zdravstvene nege, 2025)
Introduction: Self-harm is a behaviour that adolescents resort to when they do not know how to react to emotional distress. Family violence is often an important trigger for self-harm behaviour in teenagers who are faced with intense distress, fear, helplessness and loss of trust. The aim of this study was to explore the association between domestic violence and self-harm in teenagers. Methods: We searched the CINAHL, Cochrane Library, ScienceDirect and Google Scholar databases using the keywords "self-harm, family violence and adolescent" and their synonyms. We included English-language studies published between 2012 and 2023. Of the 304 hits identified, 16 studies were selected for review. We used the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) diagram to guide the review process. The data were processed using content analysis, which allowed us to review a substantial amount of text from different sources. The process began with open coding and continued with the creation of thematic sub-categories and categories. Results: The results of the literature review yielded a key thematic category of 'Impact of domestic violence on self-harm behaviour in adolescents', which was explained by three thematic subcategories: 'Childhood abuse and witnessing domestic violence', 'Parental rejection', and 'Other uncategorised factors'. Self-harm was most prevalent in adolescents who had witnessed domestic violence, experienced parental divorce, and were living in poverty or neglect. Discussion and conclusion: The results suggest that self-harm in adolescents is strongly associated with domestic violence. Teenagers often express their distress through self-harm behaviour.
Keywords: domestic violence; najstniki; nasilje v družini; samopoškodovanje; self-harm; teenagers